The moderating role of honesty-humility in the association of agreeableness with interpersonal competency: A study of managers in two countries - Wang, Ying; Dunlop, Patrick; Parker, Sharon; Griffin, Mark; Gachunga, Hazel (WILEY, 2021)
The honesty-humility factor from the HEXACO model of personality has been found to offer incremental validity in predicting several work-related criteria over the remaining factors, yet its interplay with other personality factors is rarely examined. In this study, we examined how honesty-humility (the tendency to be sincere, fair, non-materialistic, and modest) can moderate the relation between agreeableness and interpersonal competency. Specifically, drawing on the theory of self-concept, we proposed that agreeableness will have a stronger association with interpersonal competency among individuals who are higher on honesty-humility, and relatively less so among individuals who are lower on honesty-humility. Across three samples of people in managerial roles from two different cultures (Australia and Kenya), we found that honesty-humility, indeed, moderated the agreeableness—interpersonal competency relation, both when the criterion was measured by self-report (Sample 1, N = 167; Sample 2, N = 320; Sample 3, N = 296) and other-report (Sample 3, N = 195). In all three samples, the positive relation of agreeableness with interpersonal competency was strongest among those who were also higher on honesty-humility. Such an interaction effect was robust after controlling for the remaining HEXACO personality factors.